A single‐cell survey of the human glomerulonephritis. Issue 10 (22nd March 2021) - Chen, Zhejun; Zhang, Ting; Mao, Kaiqiong; Shao, Xinghua; Xu, Yao; Zhu, Minyan; Zhou, Hang; Wang, Qin; Li, Zhenyuan; Xie, YuanYuan; Yuan, Xiaodong; Ying, Liang; et al.
Abstract: Glomerulonephritis is the one of the major causes of the end‐stage kidney disease, whereas the pathological process of glomerulonephritis is still not completely understood. Single‐cell RNA sequencing (scRNA‐seq) emerges to be a powerful tool to evaluate the full heterogeneity of kidney diseases. To reveal cellular gene expression profiles of glomerulonephritis, we performed scRNA‐seq of 2 human kidney transplantation donor samples, 4 human glomerulonephritis samples, 1 human malignant hypertension (MH) sample and 1 human chronic interstitial nephritis (CIN) sample, all tissues were taken from the biopsy. After filtering the cells with < 200 genes and > 10% mitochondria (MT) genes, the resulting 14 932 cells can be divided into 20 cell clusters, consistently with the previous report, in disease samples dramatic immune cells infiltration was found, among which a proximal tubule (PT) subset characterized by wnt‐β catenin activation and a natural killer T (NKT) subset high expressing LTB were found. Furthermore, in the cluster of the podocyte, three glomerulonephritis related genes named FXYD5, CD74 and B2M were found. Compared with the mesangial of donor, the gene CLIC1 and RPS26 were up‐regulated in mesangial of IgA nephropathy(IgAN), whereas the gene JUNB was up‐regulated in podocyte of IgAN in comparison with that of donor. Meanwhile, some membranous nephropathy (MN) high expressed genes such as HLA‐DRB5, HLA‐DQA2, IFNG, CCL2 and NR4A2, which involve in highest enrichment pathway, display the cellular‐specific expression style, whereas monocyte marker of lupus nephritis (LN) named TNFSF13B was also found and interferon alpha/beta signalling pathway was enriched in B and NKT of LN comparing with donor. By scRNA‐seq, we first defined the podocyte markers of glomerulonephritis and specific markers in IgA, MN and LN were found at cellular level. Furthermore, the critical role of interferon alpha/beta signalling pathway was enriched in B and NKT of LN was declared.